2014
DOI: 10.1007/s00248-014-0421-6
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Biodegradation Through Depth-Resolved Microbial Community Functional and Structural Profiling of a Crude-Oil Contaminant Plume

Abstract: Small-scale geochemical gradients are a key feature of aquifer contaminant plumes, highlighting the need for functional and structural profiling of corresponding microbial communities on a similar scale. The purpose of this study was to characterize the microbial functional and structural diversity with depth across representative redox zones of a hydrocarbon plume and an adjacent wetland, at the Bemidji Oil Spill site. A combination of quantitative PCR, denaturing gradient gel electrophoresis, and pyrosequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…qPCR with FAE, bzdN and bamA gene primers has been repeatedly employed for the quantification of anaerobic aromatic hydrocarbon degraders in environmental samples [Beller et al, 2002[Beller et al, , 2008Fahrenfeld et al, 2014;Staats et al, 2011;Sun et al, 2014a;Winderl et al, 2008]. However, compared to cloning and sequencing, qPCR reactions need to fulfil even more rigid stringency criteria, while many of the primer sets used to date are highly degenerate ( table 1 ).…”
Section: Screening Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…qPCR with FAE, bzdN and bamA gene primers has been repeatedly employed for the quantification of anaerobic aromatic hydrocarbon degraders in environmental samples [Beller et al, 2002[Beller et al, , 2008Fahrenfeld et al, 2014;Staats et al, 2011;Sun et al, 2014a;Winderl et al, 2008]. However, compared to cloning and sequencing, qPCR reactions need to fulfil even more rigid stringency criteria, while many of the primer sets used to date are highly degenerate ( table 1 ).…”
Section: Screening Methodsmentioning
confidence: 99%
“…The results revealed a general consistency of key populations affiliated to known degraders within the genera Azoarcus and Geobacter detected via the different assays for the sites. Quantitative site monitoring of class I BCR ( bzdN ) genes of facultative anaerobes throughout the plume of the Bemidji crude oil spill has also recently been reported [Fahrenfeld et al, 2014], suggesting a significantly increased gene abundance close to the oil spill. It must be noted, however, that central catabolic genes such as bamA may be generally much more readily detectable in anoxic habitats than specific peripheral markers of aromatic hydrocarbon degradation, simply because benzoyl-CoA is a central intermediate not only in the anaerobic degradation of petrochemicals but also of humic acids, aromatic amino acids and lignin monomers [Andrade et al, 2012;Porter and Young, 2013].…”
Section: Catabolic Marker Gene-based Insights Into Environmental Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, directly analyzing in situ microbial communities at hydrocarbon-impacted sites potentially can lead to more field-relevant findings. Nextgeneration sequencing has enabled direct characterization of in situ microbial communities at selected hydrocarboncontaminated sites including sub-tidal sediment, estuary sediment, a railway refueling station, and a crude-oil contaminant plume (Acosta-González et al 2013;Fahrenfeld et al 2014;Sun et al 2013;Sutton et al 2013). Studies to date have not revealed a consistent set of hydrocarbon-associated microorganisms even when redox conditions are apparently similar; rather, characterized microbial communities vary substantially within and between sites.…”
Section: Introductionmentioning
confidence: 98%
“…Soil shelters a huge density and diversity of microbes, which are believed to participate in a variety of biogeochemical processes (Dey et al 2012;Fahrenfeld et al 2014;Stroobants et al 2014). Nitrification process is of fundamental importance for nitrogen cycling in soil ecosystems.…”
Section: Introductionmentioning
confidence: 99%